ANALISIS YURIDIS TERHADAP HAK-HAK PEREMPUAN DALAM QANUN NOMOR 6 TAHUN 2009 TENTANG PEMBERDAYAAN DAN PERLINDUNGAN PEREMPUAN DIKAITKAN DENGAN UNDANG-UNDANG NO 39 TAHUN 1999 TENTANG HAK ASASI MANUSIA DAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - SORAYA NOVIA (PREMISE LAW JURNAL, 2016)
In the international level, recognition on women’s rights as human rights is rooted in the Declaration of Human Rights in 1947 and was validated by the United Nations General Assembly on November 10, 1948. Women’s rights is also found in various legal provisions, and one of them is Law No. 39/1999 on Human Rights, Law No. 1/1974 on Marriage, and Qanun No. 6/2009 on Women Empowerment ad Protection. The objective of the research was to analyze women’s rights according to Qanun No. 6/2009 on Women Empowerment and Protection which was related to Law No. 39/1999 on Human Rights. The research used judicial normative (doctrinal) and descriptive analytic methods by describing and analyzing women’s rights in Qanun No. 6/2009 on Women Empowerment and Protection which was related to Law No. 39/1999 on Human Rights.. Keywords: Women’s Rights, Qanun No. 6/2009 on Women Empowerment and Protection, Law No. 39/1999 on Human Rights, Law No. 1/1974 on Marriage